Posiedzenia Komisji Bizantynologicznej Polskiego Towarzystwa Historycznego w roku akademickim 2023/2024 - Kochanek, Piotr (Vox Patrum, 2024)
Meetings of the Byzantine Commission of the Polish Historical Society in the Academic Year 2023/2024